Double Blinded Randomized Trial of Subcutaneous Trigeminal Nerve Stimulation as Adjuvant Treatment for Major Unipolar Depressive Disorder. Issue 5 (28th September 2018) - Gorgulho, Alessandra A; Fernandes, Fernando; Damiani, Lucas P; Barbosa, Daniel A N; Cury, Abrão; Lasagno, Camila M; Bueno, Priscila R T; Santos, Bruno F O; Santos, Renato H N; Berwanger, Otávio; Cavalcanti, Alexandre B; Teixeira, Manoel J; et al.
Abstract: BACKGROUND: More than 30% of major depressive disorder patients fail to respond to adequate trials of medications and psychotherapy. While modern neuromodulation approaches (ie, vagal nerve stimulation, deep brain stimulation) are yet to prove their efficacy for such cases in large randomized controlled trials, trigeminal nerve stimulation (TNS) has emerged as an alternative with promising effects on mood disorders. OBJECTIVE: To assess efficacy, safety, tolerability, and placebo effect duration of continuous subcutaneous TNS (sTNS) in treatment-resistant depression (TRD). METHODS: The TREND study is a single-center, double-blind, randomized, controlled, phase II clinical trial. Twenty unipolar TRD patients will receive V1 sTNS as adjuvant to medical therapy and randomized to active vs sham stimulation throughout a 24-wk period. An additional 24-wk open-label phase will follow. Data concerning efficacy, placebo response, relapse, and side effects related to surgery or electrical stimulation will be recorded. We will use the HDRS-17, BDI-SR, IDS_SR30, and UKU scales. EXPECTED OUTCOMES: The main outcome measure is improvement in depression scores using HAM-17 under continuous sTNS as adjuvant to antidepressants. Active stimulation is expected to significantly impact response and remission rates. Minor side effects are expected due to the surgical procedure and electrical stimulation. The open-label phase should further confirm efficacy and tolerability. DISCUSSION: This study protocol is designed to define efficacy of a novel adjuvant therapy for TRD. We must strive to develop safe, reproducible, predictable, and well-tolerated neuromodulation approaches for TRD patients impaired to manage their lives and contribute with society.